Cutaneous Adrenal Cortical Carcinoma Metastasis in a 6 year-old Boy - Brau-Javier, Cristina N.; Sánchez, Jorge L. (Puerto Rico Health Sciences Journal, 2010)
We report the case of a six year-old boy with a history of adrenal cortical carcinoma presenting with cutaneous metastasis. Due to the low incidence of cutaneous metastasis arising from adrenal cortical carcinoma, its diagnosis can be challenging based solely on histological analysis. Yet, the clinical history in combination with an immunohistochemical panel consisting of melan-A, alpha inhibin, D11, caretinin, neuron specific enolase, synatophysin, and chromogranin, can be useful in differentiating it from other tumors with similar cytomorphology.